2017
DOI: 10.4315/0362-028x.jfp-16-307
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7 on Romaine Lettuce When Inoculated in a Fecal Slurry Matrix

Abstract: A field trial was conducted in July 2011 to quantify the inactivation rate of Escherichia coli O157:H7 when mixed with fecal slurry and applied to romaine lettuce leaves. Lettuce was grown under commercial conditions in Salinas Valley, CA. One-half milliliter of rabbit fecal slurry, containing 6.3 × 10 CFU of E. coli O157:H7, was inoculated onto the upper (adaxial) surface of a lower leaf on 240 heads of lettuce within 30 min after a 2.5-h irrigation event. Forty-eight romaine lettuce heads were collected per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 30 publications
5
30
3
Order By: Relevance
“…While there have been an abundance of studies to model bacterial survival kinetics (Chase et al, 2017, Salazar et al, 2017), transfer dynamics (Atwill et al, 2015), and preharvest risk factors (Pagadala et al, 2015) linked to raw produce consumption (Ibekwe et al, 2005; Pachepsky et al, 2016; Tian et al, 2012), relatively little is known about the potential risk inherent in agricultural water supplies.…”
mentioning
confidence: 99%
“…While there have been an abundance of studies to model bacterial survival kinetics (Chase et al, 2017, Salazar et al, 2017), transfer dynamics (Atwill et al, 2015), and preharvest risk factors (Pagadala et al, 2015) linked to raw produce consumption (Ibekwe et al, 2005; Pachepsky et al, 2016; Tian et al, 2012), relatively little is known about the potential risk inherent in agricultural water supplies.…”
mentioning
confidence: 99%
“…Manuscript to be reviewed to experience high levels of log-reduction under summer field conditions (McKellar et al 2014;Moyne et al 2011). However, a recent study under California summer conditions found that E. coli O157:H7 mixed with a fecal slurry to simulate fecal splash during foliar irrigation exhibited reduced rates of inactivation in contrast to this earlier work (Chase et al 2017). In addition, Weller et al (2017b) replicated these findings of extended survival of E. coli when the bacteria were mixed in a fecal slurry under growing conditions typical of upstate New York.…”
Section: Introductionmentioning
confidence: 84%
“…var. longifolia) was grown under commercial conditions in the Salinas Valley, California with plant thinning, weed removal, and irrigation being performed as needed up to field inoculation described by Chase et al (2017). The lettuce was planted on June 12 and August 14 for the summer and fall trials, respectively.…”
Section: Field Site and Lettuce Plotmentioning
confidence: 99%
See 2 more Smart Citations